Molecular and genetic features of a bla NDM−1 and bla SHV−12 coharboring hypermucoviscous Klebsiella pneumoniae of serotype K2 and ST65 - Yuting Kang; Qiujie Li; Wanting Ma; Chao Xu; Zhuoran Qiu; Wei Jia; Pengtao Wang (Annals of Clinical Microbiology and Antimicrobials)
Abstract Purpose This study aimed to assess the resistance phenotype, virulence phenotype, and genetic characteristics of a bla NDM−1 and bla SHV−12 co-harboring ST65 K2 Klebsiella pneumoniae (KP114), which was isolated from General hospital of Ningxia Medical University. Methods Antibiotic susceptibility test was determined by Vitek 2 Compact system. Multilocus Sequence typing (MLST), antimicrobial resistance and virulence genes were examined by PCR and Sanger sequencing. The virulence of KP114 was evaluated through string test, macrophage phagocytosis assay, serum resistance assay, and mouse infection model. Whole-genome sequencing was performed for further analysis of genetic information. Results The presence of the bla NDM−1 and bla SHV−12 genes in KP114 confered resistance to multi-antibiotics. The hypervirulence of KP114 was demonstrated through various in vitro experiments and in vivo mouse infection model. KP114 was found to harbor two distinct plasmids: a drug-resistant plasmid (pKP114-NDM), classified as the IncX3 type, which contained various transfer elements including type IV coupling protein (T4CP) and type IV secretion system (T4SS), and a virulence plasmid (pKP114-vir) that exhibited a high sequence similarity with pLVPK. The results of the conjugation experiment showed that resistance and virulence traits were successfully transferred from KP114 to Escherichia coli EC600 and J53. Conclusions We reported a Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) strain of ST65 K2 serotype carrying the bla NDM−1 and bla SHV−12, which exhibited hypervirulence and drug resistance with potential for transmission. This finding allows improved clinical surveillance and control of this clone, thereby holding considerable value for clinical treatment.